Comparison of StemPrintER with Oncotype DX Recurrence Score for predicting risk of breast cancer distant recurrence after endocrine therapy. (March 2022) - Pece, Salvatore; Sestak, Ivana; Montani, Francesca; Tillhon, Micol; Maisonneuve, Patrick; Freddi, Stefano; Chu, Kim; Colleoni, Marco; Veronesi, Paolo; Disalvatore, Davide; Viale, Giuseppe; Buus, Richard; et al.
Abstract: Objective: Molecular tests predicting the risk of distant recurrence (DR) can be used to assist therapy decision-making in oestrogen receptor–positive (ER+) and human epidermal growth factor receptor 2–negative (HER2-) breast cancer patients after considerations of standard clinical markers. The Oncotype DX Recurrence Score (RS) is a widespread tool used for this purpose. Here, we compared the RS with the StemPrintER Risk Score (SPRS), a novel genomic predictor with a unique biological basis in its ability to measure the expression of cancer stemness genes. Materials and methods: We benchmarked the SPRS vs . RS, alone or in combination with clinicopathological variables expressed by the Clinical Treatment Score (CTS), for the prognostication of DR in a retrospective cohort of 776 postmenopausal patients with ER+/HER2-breast cancer enrolled in the translational arm of the randomised Arimidex, Tamoxifen, Alone or in Combination (ATAC) trial. Likelihood ratio (LR) with χ 2 test and C-index were used to assess prognostic performance for the entire ten-year follow-up period and in early (0–5 years) and late (5–10 years) intervals. Results: In all patients, the SPRS provided significantly more prognostic information than the RS for ten-year DR prognostication (C-index = 0.688, LR-χ 2  = 33.4 vs. C-index = 0.641, LR-χ 2  = 22.1) and for late (5–10 years) DR prognostication (C-index = 0.689, LR-χ 2  = 18.8 vs. C-index = 0.571, LR-χ 2  = 4.7). The SPRS also provided more prognostic information than the RS when added to the CTS in all patients (CTS + SPRS: LR-Δχ 2  = 14.9; CTS + RS: LR-Δχ 2  = 9.7) and in node-negative patients (CTS + SPRS: LR-Δχ 2  = 11.7; CTS + RS: LR-Δχ 2  = 6.6). Conclusions: In postmenopausal ER+/HER2- breast cancer patients, SPRS provided more prognostic information than RS for DR when used alone or in combination with the CTS. The SPRS could therefore potentially identify high-risk patients, who might benefit from aggressive treatments, from low-risk patients who might safely avoid adjuvant chemotherapy or prolongation of endocrine therapy. Highlights: The StemPrintER Risk Score (SPRS) is a stem cell–based prognostic test for breast cancer. The SPRS was validated in ER+/HER2-postmenopausal women from the TransATAC cohort. The SPRS was highly prognostic for early (0–5 yr) and late (5–10 yr) distant recurrence. The SPRS was benchmarked against the Oncotype DX Breast Cancer Recurrence Score (RS). The SPRS has the potential to help guide clinical decision-making in breast cancer.